Power Market Sophistication and Sector Outcomes : A Focus on Social Performance, Electricity Reliability, and Renewable Energy Penetration - Doumbia, Djeneba (World Bank, Washington, DC, 2021)
This paper exploits a novel and comprehensive dataset on power market structure over 1989–2020 to analyze the relationship between power market sophistication—defined as the move toward a more competitive market—and final sector outcomes: social performance, electricity reliability, and renewable energy penetration. Unlike most previous studies on the performance of power sector reforms, the paper relies on the de facto implementation of reforms rather than de jure reform adoption. The results of panel regression models suggest that moving from vertically integrated utility models toward more sophisticated power markets is associated with higher electricity access, better consumer affordability, larger renewable energy penetration, and lower system average interruption duration index. The results also highlight that, for certain steps in power market sophistication, improvements in sector outcomes are greater. For instance, moving from vertically integrated utility models to single buyer models is associated with relatively larger improvements in access to electricity and electricity reliability, while moving from wholesale competition to retail competition models is associated with a relatively larger penetration of renewable energy.